Determining the Natural Disaster Diversity of Van Province by Fine Kinney Risk Assessment Method (FK-RAM) - Bülent Matpay; Sacit Mutlu (Doğal Afetler ve Çevre Dergisi)
The study area covers the province of Van in eastern Turkey. There is a limited number of studies conducted in Turkey using the risk assessment method (RAM). RAM, which was previously applied by researchers for Bitlis, was applied for the first time for Van province. The study carried out in Van, which has similar geographical conditions and disaster diversity to Bitlis, aimed to fill a gap. There are many parameters that make Van province risky in terms of natural disasters. Neotectonics, geology, geomorphology and climatic characteristics of the province are among these parameters. In the study, temporal and spatial analyses were made using avalanche, landslide, rock fall and flood parameters and risk classifications were revealed. Fine-Kinney RAM has been used in many disciplines, especially in occupational health and safety studies. In terms of the diversity of natural disasters in the field, there are points with "Acceptable risk" characteristics as well as "Very high risk" and "High risk" areas have been identified. It is calculated that the southwestern and northwestern parts of Van province have "Very high risk" and "High risk" in terms of landslides, avalanches and rock falls due to its highly sloping topographical structure and meteorological conditions. Morphologically, it was calculated that the slopes where the slope decreases, at the mouths of the tributaries connected to the main tributaries and towards the valley floors carry a "High risk" of flooding. Finally, high-risk areas in Van were identified by risk rating of four natural disaster types. Therefore, it is recommended that risk assessment results should be taken into consideration with a proactive perspective. In this way, it is clear that loss of life and property will be prevented.